Fenton-like degradation of sulfathiazole using copper-modified MgFe-CO3 layered double hydroxide - de Melo Costa-Serge, Nayara [UNESP]; Gonçalves, Rosembergue Gabriel Lima [UNESP]; Rojas-Mantilla, Hernán Dario [UNESP]; Santilli, Celso Valentim [UNESP]; Hammer, Peter [UNESP]; Nogueira, Raquel Fernandes Pupo [UNESP] (Elsevier, 2021)
The catalytic activity of layered double hydroxides, with and without insertion of copper, was evaluated in a heterogeneous Fenton process for degradation of the antibiotic sulfathiazole (STZ). The characterizations with different techniques revealed lamellar structures formed by stacking of layers containing magnesium, iron, and copper cations. The insertion of copper in the lamellar structure increased the specific area of the material and the degradation kinetics, achieving complete STZ removal after 90 min. X-ray photoelectron spectroscopy analysis showed the presence of Cu(II) and Cu(I) surface sites, which contributed to the generation of hydroxyl and hydroperoxyl/superoxide radicals. It also indicated an increase of Cu(I) content after use. For both materials, but specially for LDH without copper, addition of tert-butyl alcohol and p-benzoquinone hindered STZ degradation, indicating the importance of hydroxyl and hydroperoxyl/superoxide radicals in the degradation process, respectively. These results demonstrated the potential of copper-modified MgFe-CO3 as a catalyst for the degradation of emerging contaminants, offering the benefits of easy preparation and high efficiency in the Fenton process.
Keywords: Copper Fenton; Hydroperoxyl/superoxide radical; Hydroxyl radical; Pyroaurite; Vis-LED